Analysis of crack propagation in double cantilever beam tests of multidirectional laminates - Morais, A.B. de
This paper presents numerical analyses of crack propagation in double cantilever beam (DCB) tests of multidirectional laminates. Three-dimensional finite element models were used for application of the virtual crack closure technique and for simulation of crack growth with a progressive damage model. The analyses were concerned with three features that may affect the measurements of the mode I critical strain energy release rate GIc : residual stresses, mode-mixity and curved delamination fronts. The results showed that the effects of those features could be minimised by a proper selection of specimen stacking sequences. The suitability of other DCB specimens proposed in the literature to avoid intralaminar damage and crack jumping was also evaluated.